Controllable synthesis of N-doped carbon nanoparticles with proper electrical conductivity for excellent microwave absorption performance. (February 2023) - Dong, Wenqi; Li, Xueai; Jin, Kexin; Shi, Yuning; Wang, Chunsheng; Guo, Wanchun; Tian, Kesong; Wang, Haiyan
Graphical abstract: Highlights: N -doped carbon nanoparticles are synthesized by heat treatment on phenolic resin. The σ of carbon were tuned by morphology, diameter and graphitization degree. Microwave absorption (MA) properties of carbon were intensively affected by the σ . The total σ of composites with order of magnitude of 10 -1 S/m is proper for MA. Carbon nanoparticles with σ of 0.61 S/m show effective bandwidth of 6.7 GHz. Abstract: Carbonaceous materials play significant function in microwave absorption owing to their unique properties. However, it is still a challenge to control and understand the influence of electrical conductivity ( σ ) and polarization on microwave absorption. Herein, N -doped carbon with proper σ modified by morphology, particle size and graphitization degree are controllably synthesized. A higher σ is beneficial to a higher attenuation constant, but a σ that is too high will lead to enhancement of the primary reflection of microwave, resulting in impedance mismatch. The composite of carbon nanoparticles with an electrical conductivity of 0.61 S/m exhibits excellent microwave absorption performance with a strong reflection loss of −68.1 dB and a wide response effective bandwidth of 6.7 GHz (reflection loss over −10 dB) at a thickness of 2.60 mm. This research indicates that controlling the electrical conductivity in composites is an effective way to tune microwave absorption.